2021
DOI: 10.3390/cryst11101216
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis of Ge1−xSnx Alloy Nanoparticles for Optoelectronic Applications

Abstract: Compositionally controlled, light-emitting, group IV semiconductor nanomaterials have potential to enable on-chip data communications and infrared (IR) imaging devices compatible with the complementary metal−oxide−semiconductor (CMOS) technology. The recent demonstration of a direct band gap laser in Ge-Sn alloys opens avenues to the expansion of Si-photonics. Ge-Sn alloys showed improved effective carrier mobility as well as direct band gap behavior at Sn composition above 6–11%. In this work, Ge1−xSnx alloy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…Moreover, the Ge 0.95 Sn 0.05 nanocrystals of a 10 nm diameter exhibited a 25% higher capacity than Ge nanoparticles in anode materials [ 30 ]. A solution-based approach [ 31 ] proposes the synthesis of Ge/Sn alloy nanoparticles with a diameter of 3–25 nm and atomic tin content from 5 to 40% [ 32 , 33 ]. It was demonstrated that pulsed laser deposition and gas-phase laser photolysis allowed for producing Ge/Sn micro- and nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the Ge 0.95 Sn 0.05 nanocrystals of a 10 nm diameter exhibited a 25% higher capacity than Ge nanoparticles in anode materials [ 30 ]. A solution-based approach [ 31 ] proposes the synthesis of Ge/Sn alloy nanoparticles with a diameter of 3–25 nm and atomic tin content from 5 to 40% [ 32 , 33 ]. It was demonstrated that pulsed laser deposition and gas-phase laser photolysis allowed for producing Ge/Sn micro- and nanoparticles.…”
Section: Introductionmentioning
confidence: 99%